Diabetes mellitus and hearing loss - Yuxin Deng; Sen Chen; Jun Hu (BMC, 2023)
Abstract Diabetes mellitus (DM) is a major disease threatening human health and its incidence is increasing year on year. As a chronic complication of DM, hearing loss mostly occurs undetectably. However, the mechanism of this diabetes-related hearing loss (DRHL) remains unclear and there is no effective clinical treatment. Studies of animal or human pathology show that DM causes damage to the blood vessels, spiral ganglion neurons, afferent nerve fibers, the organ of Corti, and the stria vascularis of the inner ear. In recent years, more advances in pathological research have revealed the possible mechanism of DRHL. In addition, a large number of clinical studies suggest that the duration and severity of DM are closely related to the incidence and severity of DRHL. This review focuses on the relationship between DM and hearing loss. The clinical audiological characteristics of diabetic patients, risk factors for DRHL, typical pathology, and potential interventions of DRHL are summarized. This will help reveal the pathogenesis and intervention approaches for DRHL.